Teaching The Holy Quran to Young Learners (7-12 Years Old) - Andi Irlina (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Teaching the holy Qur’an to young learners is very important to keep children healthiness, physically or mentally. Young learner teacher should employ several techniques or methods that interest children. This article explores some methods for teaching the holy Quran to young learner. The teachers should provide the appropriate way, techniques or methods in teaching how to read and how to memorize the holy Qur’an well, appropriate techniques and methods can help children to be able to learn or memorize the holy Qur’an easily such as Baghdadiyah method, Iqra, qiro’ati, albarqy, tilawati, and hambalis method. In teaching recitation and memorization of the Qur’an to young learners the methods are talqin musyafahah and takrir methods, deposited method, and muraja’ah method (repetition).